2021
DOI: 10.25115/eea.v39i3.4717
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Social Communication as a Tool of Social Work under the Influence of Digitalization

Abstract: Modern society is a complex multilevel system in which many people coexist with their values and problems. And not all contemporary society members can adapt to its many rules, so sometimes people find themselves outside the community and need the help of social services. The study aims to improve social work tools as an element of social communication under the influence of digitalization. As the research has shown, changing conditions of reality make their adjustments to all aspects of society, including soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We recognize the procedure of acquiring English-language CCCs on the personal, interpersonal and synergetic levels. At the same time, the analysis of the self-reflection method applied to the G1 and G2 groups of respondents covered the attitudes of some of them to digitalization and the latest socio-media tools (Mitchuk et al, 2021). The importance of the latest tools in the educational linguistic environment in previous decades is emphasized (Hymes, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recognize the procedure of acquiring English-language CCCs on the personal, interpersonal and synergetic levels. At the same time, the analysis of the self-reflection method applied to the G1 and G2 groups of respondents covered the attitudes of some of them to digitalization and the latest socio-media tools (Mitchuk et al, 2021). The importance of the latest tools in the educational linguistic environment in previous decades is emphasized (Hymes, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we note the researchers' opinions which differ in terms of the choice of certain interactive methods, tools and social media applications that are most effective (Haerazi, Utama & Hidayatullah, 2020). In particular, it is about igniting scientific interest in updating the interactive context of research, which carries elements of novelty (Sabat, 2020) through social media applications (Mitchuk et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Adaptation of ATC management to environmental conditions requires effective current methods and tools of support and protection, as the development of an effective model of innovative financial management strategy. Research in this area has almost not been conducted, so we should expect further development of the discussion around the creation of the importance of a particular factor in the internal or external environment [8]. In fact, such interaction should be achieved in the implementation of an innovative financial management strategy in terms of amalgamated territorial communities (ATC), where community and the state are stakeholders.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that the reason for this is that in the pre-pandemic period, the importance of these factors was underestimated, as companies conducted marketing campaigns mostly offline in direct contact with the consumer. The situation has changed dramatically, which makes it necessary and urgent to study the impact of social media marketing on the financial stability of companies [8].…”
Section: Introductionmentioning
confidence: 99%